Secure Model against APT in m-Connected SCADA Network - Si-Jung Kim; Do-Eun Cho; Sang-Soo Yeo (International Journal of Distributed Sensor Networks)
Supervisory control and data acquisition (SCADA) networks for the remote control and operation of various industrial infrastructures are currently being used as main metropolitan infrastructures, especially smart grid and power plants. Most of the existing SCADA networks have fortified securities because of their powerful access control based on closed and private networks. However, recent SCADA networks are frequently connected to various IT-based systems and also to other conventional networks, in order to achieve the operational convenience of SCADA systems, as well as the execution requirements of various applications. Therefore, SCADA systems have acute needs for secure countermeasures against the ordinary network vulnerabilities and for tangible preparations against ever-changing intrusion attacks such as advanced persistent threat (APT). This paper introduces the concept of m-connected SCADA networks, analyzes various security vulnerabilities on such networks, and finally proposes an integrated secure model having an APT managing module and a rule-based intrusion detection system (IDS) for internal and external network access.